Javanese Indigenous Healing for Physical and Mental Health - Cintami Farmawati; Endro Puspo Wiroko; Hairenanorashikin Sharip; Nada Ibrahim (JOUSIP: Journal of Sufism and Psychotherapy, 2022)
The indigenous of Javanese is very complex, there are a lot of things to pay attention to, including how to be healthy. In the context of this study, it aims to describe the process of Javanese indigenous healing for physical and mental health. To achieve this goal, this study uses a literature study by collecting data and information about indigenous healing and health of the Javanese. The results of research explain that the concept of Javanese indigenous healing is able to maintain physical and mental health. This research shows that Javanese indigenous healing system for physical health written in the manuscripts of Javanese such as Serat Primbon Jampi Jawi, Serat Primbon Racikan Jampi Jawi, Serat Centhini, Serat Munasiyat Jati and other Javanese manuscripts. In addition, the philosophy of the Javanese community such as nrimo ing pandum is very relevant to the concept of mental health. Maintaining mental health is very important so that the soul is calm and peaceful, so that it can enjoy everyday life and respect others. The people of Javanese who are healthy and feel happiness in their life have the characteristics of being sepuh, wutuh and tangguh. Achieving a healthy personal status and finding happiness is done by holding on to a balanced mind, feeling, word and deed.